1992
DOI: 10.1007/bf00199976
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal patchiness in Mediterranean evergreen sclerophylls

Abstract: Midday depression of net photosynthesis and transpiration in the Mediterranean sclerophylls Arbutus unedo L. and Quercus suber L. occurs with a depression of mesophyll photosynthetic activity as indicated by calculated carboxylation efficiency (CE) and constant diurnal calculated leaf intercellular partial pressure of CO2 (Ci). This work examines the hypothesis that this midday depression can be explained by the distribution of patches of either wide-open or closed stomata on the leaf surface, independent of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Similar results were observed in A. unedo, throughout an entire year, by Beyschlag et al (1992), although in the same species and similar environmental conditions Raschke and Resemann (1986) observed a broad temperature optimum for photosynthesis. These latter authors concluded that rising leaf temperature could account for not more than 10% of the observed decline in A max at midday.…”
Section: Non-diffusional Limitationssupporting
confidence: 90%
“…Similar results were observed in A. unedo, throughout an entire year, by Beyschlag et al (1992), although in the same species and similar environmental conditions Raschke and Resemann (1986) observed a broad temperature optimum for photosynthesis. These latter authors concluded that rising leaf temperature could account for not more than 10% of the observed decline in A max at midday.…”
Section: Non-diffusional Limitationssupporting
confidence: 90%
“…Analogously, patchy stomatal behaviour at the canopy scale (e.g., inactivity of a proportion of sun leaves), should provide decreasing water‐use efficiency at the canopy level. Stomatal patchiness has been identified as a common phenomenon in Mediterranean species (Beyschlag et al ., 1992). Yet, the impact of stomatal patchiness on whole canopy gas exchange has never been assessed (Beyschlag & Eckstein, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, large drought‐induced reductions of photosynthetic capacities of more than 70%, as estimated for the PuĂŠchabon and Arca di Noè site, seem unlikely since in drought‐adapted species only minor changes in mesophyll capacities have been found in laboratory studies [ Kaiser , 1987; Chaves , 1991; Cornic , 1994]. Instead, patchy stomatal closure over a large portion of the leaf surface has been observed for Mediterranean species as a consequence of drought [ Beyschlag et al , 1992; Beyschlag and Eckstein , 1998] and also for Quercus ilex L. [ Genty and Meyer , 1995] so that Roupsard et al [1996] concluded that stomatal closure is probably the main factor reducing CO 2 availability in the chloroplasts during drought (p. 252).…”
Section: Discussionmentioning
confidence: 99%
“…Harley and Tenhunen, 1991;Lawlor, 1995], (2) the induction of stomatal patchiness (i.e., nonnormal distribution of stomatal apertures [cf. Beyschlag et al, 1992;Beyschlag and Eckstein, 1998;Buckley et al, 1999]). The first hypothesis has meanwhile received support from leaf-level studies [Xu and Baldocchi, 2003].…”
Section: Discussionmentioning
confidence: 99%